Game Edukasi Pengenalan Warna Untuk Anak PAUD Menggunakan Unity 3D Dengan Metode Design Thinking Studi Kasus PAUD-KB-TK GBKP Salsalina - Ginting, Agung Suka; Fachri, Barany; Badawi, Afif (Universitas Islam Negeri Sumatera Utara, 2025)
Educational games are effective tools for combining entertainment and education for children, especially in the context of Early Childhood Education (ECE). The introduction of colors is an essential aspect of children's cognitive development; however, conventional teaching methods often lack engagement, hindering the learning process. This study demonstrates that the application of technology, such as educational games, can enhance children's motivation and involvement in learning. By utilizing the Unity 3D platform, developers can create interactive and engaging learning environments. The Design Thinking method is employed in this research to design solutions that focus on user needs, based on a deep understanding of children. Usability aspects are tested using a Likert scale, encompassing learnability, efficiency, memorability, error prevention, and user satisfaction. The results indicate that the designed educational game provides an enjoyable and effective learning experience in introducing color concepts to children.